The Wretched of the Earth - Fanon, Frantz (USA; Penguin Books)
Frantz Fanon's seminal work on the trauma of colonization, "The Wretched of the Earth" made him the leading anti-colonialist thinker of the twentieth century. This "Penguin Modern Classics" edition is translated from the French by Constance Farrington, with an introduction by Jean-Paul Sartre. Written at the height of the Algerian war for independence from French colonial rule and first published in 1961, Frantz Fanon's classic text has provided inspiration for anti-colonial movements ever since, analysing the role of class, race, national culture and violence in the struggle for freedom. With power and anger, Fanon makes clear the economic and psychological degradation inflicted by imperialism. It was Fanon, himself a psychotherapist, who exposed the connection between colonial war and mental disease, who showed how the fight for freedom must be combined with building a national culture, and who showed the way ahead, through revolutionary violence, to socialism. Many of the great calls to arms from the era of decolonization are now of purely historical interest, yet this passionate analysis of the relations between the great powers and the 'Third World' is just as illuminating about the world we live in today.
English
Keywords: 20th century; Colonised people; HN1-995 Social history and conditions. Social problems. Social reform